Kreacja - obraz - mit. Wyobrażenie kobiety w twórczości Stanisława Staszewskiego = Creation - image - myth. The female figure in Stanisław Staszewski`s oeuvre - Kubiak, Maciej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of this article is to draw attention to the way in which the figure of a woman is presented in the works of Stanisław Staszewski. In his characteristic way, the artist refers to the familia figures from his own environment, filtering private acquaintances through his literary and musical awareness. The sources of his perception of women, the process of mythologizing their figures, the references to the archetypes and culturally conditioned models of women, in Staszewski`s case, go back to the works of the Young Poland period, whose motifs, narratives, and poetics are used by the artist to create an individual literary style.
Keywords: mitologizacja; kobieta; piosenka; Staszewski, Stanisław (1925-1973); 20 w.; mythologization; woman; song